Understanding Japan’s Civil Service System: Norms, Meritocracy, and Institutional Change - Zuliansyah P. Zulkarnain; Eko Prasojo (Policy & Governance Review, 2021)
This article aims to elucidate the tradition of Japan’s public administration emphasizing the civil service system. A number of studies explain the impact of the tradition (norms, values, and institutions), in shaping the process and result of public administration reform. By applying the historical institutionalism perspective, this study reveals how the legacy of the past, the tradition promoted by the Meiji Restoration, creates the new tradition of public administration. This study selects Japan as a typical case representing Asian developmentalists. The remarkable Meiji restoration marked the process of adoption and adjustment of the Germanic traditions in the bureaucracy modernization. Norm institutionalization has established the new norms and civil service system. The basic norms consist of legality, consensus, and seniority. It develops the "kyaria" denoting recruitment, selection, and promotion influenced by seniority, long term performance, and prestigious university recommendation and produces competent and dominant mandarins in the policy process. However, the parliament continuously initiates the reform to reduce the mandarin's domination and heighten political control over the bureaucracy. The reform has not yet changed the power balance of two institutions since the ”kyaria's” embeddedness in Japan's polity produces two consequences. First, it contributes to public administration modernization. The mandarin’s outstanding performance increases political legitimacy and social acceptance to the "kyaria"system. Second, the parliament cannot drastically reduce the mandarin’s role since the lifetime employment model enriches them with knowledge and experience of the government affairs. Conducting cautious reform and, at the same time, working closely with the mandarin are the primary reform strategy of the parliament.